2019
DOI: 10.3390/antiox8100471
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Mediated Mechanism of Chemoresistance in Cancer Cells

Abstract: Cellular reactive oxygen species (ROS) status is stabilized by a balance of ROS generation and elimination called redox homeostasis. ROS is increased by activation of endoplasmic reticulum stress, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase family members and adenosine triphosphate (ATP) synthesis of mitochondria. Increased ROS is detoxified by superoxide dismutase, catalase, and peroxiredoxins. ROS has a role as a secondary messenger in signal transduction. Cancer cells induce fluctuations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 174 publications
1
60
0
Order By: Relevance
“…The result of an imbalance between oxidants and antioxidants is oxidative stress, the consequences of which are oxidative modifications of lipids, nucleic acids, and proteins. This results in changes in the structure of the above molecules and, as a result, disrupts their molecular interactions and signal transduction pathways [39]. Oxidative modifications play an important role in the functioning of redox-sensitive transcription factors (including Nrf2 and the nuclear factor kappa B (NFκB).…”
Section: The Consequences Of Direct Antioxidant Action Of Cbdmentioning
confidence: 99%
“…The result of an imbalance between oxidants and antioxidants is oxidative stress, the consequences of which are oxidative modifications of lipids, nucleic acids, and proteins. This results in changes in the structure of the above molecules and, as a result, disrupts their molecular interactions and signal transduction pathways [39]. Oxidative modifications play an important role in the functioning of redox-sensitive transcription factors (including Nrf2 and the nuclear factor kappa B (NFκB).…”
Section: The Consequences Of Direct Antioxidant Action Of Cbdmentioning
confidence: 99%
“…Furthermore, increased oxidative stress is an important factor leading to abnormal intracellular signal transduction (17,18). ROS can induce continuous activation of pSTAT3, NF-κB and mitogen-activated protein kinase (MAPK) signaling pathways (16,(19)(20)(21)(22)(23)(24) and promote the growth of certain cancer, including ccRCC, melanoma and liver cancer, regulate angiogenesis, and accelerate tumor metastasis by promoting the expression of a series of proliferation-and metastasis-related genes, including cyclinD1 and matrix metalloproteinases (MMPs) (16,(25)(26)(27).…”
Section: G6pd Facilitates Clear Cell Renal Cell Carcinoma Invasion Bymentioning
confidence: 99%
“…It has been reported that ROS dysregulation plays crucial impact on abnormal intracellular signal transduction [21,22]. ROS could stimulate continuous activation of pSTAT3, NF-κB and MAPK signals [19,[23][24][25], and promote the occurrence and development of various types of cancer, including RCC, shin cancer and lung cancer [19,26,27]. NF-κB signaling over-activation has been described to contribute to RCC cell migration and invasion [28], and the high expression level of pSTAT3 S727 is expected to be an independent prognostic molecule for ccRCC patients [29,30].…”
Section: Introductionmentioning
confidence: 99%